Pengaruh Orientasi Bangunan terhadap Suhu Termal dan Kelembaban pada Unit Rusunawa Keudah di Banda Aceh - Sanova, Widia; Idawati, Dyah Erti; Zahrah, Aghnia; Maharani, Lisa; Kh, Fithria Zahwa (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
The primary function of residential spaces is to ensure occupant comfort, with thermal conditions playing a key role. Thermal comfort is achieved when body temperature balances with the surrounding environment, influenced mainly by temperature and humidity. This study examines the impact of building orientation on thermal comfort, particularly temperature and humidity, based on Indonesian National Standard (SNI). A quantitative method was used, combining field measurements and ANSYS 2021 R2 simulations. The study focused on four rental apartment (Rusunawa) units in Keudah, Banda Aceh, with different orientations. Measurements were taken over three consecutive days in March 2024, recording indoor temperature and humidity. Results show that building orientation does not significantly affect thermal conditions. The lowest recorded temperature was 28ºC in Block D (east-oriented), while the least comfortable unit had the highest temperature of 35.5ºC in Block B (west-oriented). The lowest humidity (66.2%) was recorded in Block C, while the highest (85%) was found in Blocks B and D.